Acceptance of Data Sharing in Smartphone Apps from Key Industries of the Digital Transformation: A Representative Population Survey for Germany - Svenja Mohr; Janis Cloos (Philipps-University Marburg, School of Business and Economics, 2021)
The use of smartphone apps has numerous advantages for app providers and users. However, the users of many smartphone apps are confronted with a trade-off between usage benefits and preferences for personal data protection. We investigate the acceptability of data sharing in different hypothetical scenarios describing five types of these apps from key industries of the digital transformation. In a representative survey for the German population (N=1,013), we examine to what extent the acceptance of data sharing is influenced by potential recipients, collected information attributes, and the promoted benefits of data sharing. We differentiate the promoted benefits in two treatments according to monetary (or personal) and environmental (or public) benefits. Our results show no treatment effects but significant differences in acceptance values for different recipients and information attributes. We further observe that participants with stronger green consumption values, participants with a stronger risk propensity, men, and younger participants show a higher acceptance towards data sharing in the described scenarios.
Keywords: O33; Q18; C83; L86; M31; M37; 330; privacy; digitalization; digital transformation; representative survey; data protection; environmental attitudes